2017
DOI: 10.1038/s41598-017-07494-0
|View full text |Cite
|
Sign up to set email alerts
|

Bee-derived antibacterial peptide, defensin-1, promotes wound re-epithelialisation in vitro and in vivo

Abstract: Royal jelly (RJ) has successfully been used as a remedy in wound healing. RJ has multiple effects, including antibacterial, anti-inflammatory and immunomodulatory activities, in various cell types. However, no component(s) (other than antibacterial) have been identified in RJ-accelerated wound healing. In this study, we demonstrate that keratinocytes are responsible for the elevated production of matrix metalloproteinase-9 (MMP-9) after incubation with a water extract of RJ. Furthermore, the keratinocyte migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 44 publications
2
59
0
1
Order By: Relevance
“…A protein fraction, mainly containing MRJP-2,3,7 have the potential to influence wound healing bioactivity by stimulating keratinocyte growth and migration suggests that these proteins promote the development of new wound healing medication [130]. The defensin-1 peptide in RJ contributes to skin regeneration and cutaneous wound closure by increasing matrix metalloproteinase-9 secretion and keratinocyte migration [131].…”
Section: Wound Healing Activitymentioning
confidence: 99%
“…A protein fraction, mainly containing MRJP-2,3,7 have the potential to influence wound healing bioactivity by stimulating keratinocyte growth and migration suggests that these proteins promote the development of new wound healing medication [130]. The defensin-1 peptide in RJ contributes to skin regeneration and cutaneous wound closure by increasing matrix metalloproteinase-9 secretion and keratinocyte migration [131].…”
Section: Wound Healing Activitymentioning
confidence: 99%
“…Moreover defensin-1 promotes reepithelization and wound closure. Similarly as in honey, defensin-1 is responsible for cutaneous wound closure by enhancing keratinocyte and MMP-9 secretion [69]. Royal jelly is effective in the treatment of wounds, and is successfully used in cosmetics for problem skin care.…”
Section: Royal Jellymentioning
confidence: 99%
“…Many studies have reported that royal jelly possesses a plethora of biological activities, including antimicrobial [6][7][8][9], anti-inflammatory [10], anti-tumour [11], antioxidant [12], immunomodulatory [13] and growthpromoting [14] effects. What is more, it has been documented to be used in folk medicine for the facilitation of wound healing since ancientry [15]. Although some studies have indicated that topical application of royal jelly can shorten the period of infected or uninfected wound healing in animal models and even diabetic foot ulcers [16][17][18], the substances and precise mechanisms associated with wound healing are still poorly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have indicated that topical application of royal jelly can shorten the period of infected or uninfected wound healing in animal models and even diabetic foot ulcers [16][17][18], the substances and precise mechanisms associated with wound healing are still poorly investigated. Previous studies merely reported that royal jelly components, especially 10-hydroxy-2-decenoic acid (10-HDA) and defensin-1, might accelerate wound healing through anti-inflammation, promoting synthesis of growth factors, or migration of skin fibroblasts or keratinocytes [15,[19][20][21][22]; MRJPs could induce proliferation of several human cell lines [23].…”
Section: Introductionmentioning
confidence: 99%